The development of participatory institutions in Paraguay: a tool for democratization or state control? - Gustavo Setrini; Liliana Rocío Duarte-Recalde (Cahiers des Amériques Latines)
Public policies in Paraguay have been historically characterized by their clientelistic nature. However, in 2016 the Ministry of Planning introduced participatory planning mechanisms that oblige local governments to submit development plans prepared by Municipal Development Councils as a condition for the disbursement of public funds. Can participation democratize local politics? After reviewing the history of participatory institutions in Paraguay and analyzing the political and bureaucratic conditions under which the State began to promote participatory local development planning nationwide, we conclude that the institutional power granted to the new Councils is insufficient to meaningfully redistribute power from local party officials to civil society.